(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study focused on the legal system of companies owned by the Public Investment Fund, and was divided into two sections, and the first section dealt with the legal system of companies owned by the Public Investment Fund, divided into two requirements, and focused on the first requirement legal system for companies owned by the Public Investment Fund, and focused on the second requirement legal personality of companies owned by the Public Investment Fund, and the second section focused on companies owned by the Public Investment Fund, and divided into two requirements, the first of which is the establishment and management of companies owned by the Public Investment Fund. Public investments, the second requirement reviews the control and expiry of companies owned by the Public Investment Fund. The main objective of the study is to know the legal nature of the companies owned by the Public Investment Fund, and to know the type of legal personality granted to them to know whether they fit the description of government agencies or not. And to know the supervisory authority to which the companies owned by the Public Investment Fund are subject. The study found that the companies owned by the Public Investment Fund are private commercial companies and have their own legal personality independent of the personality of their owner - the Public Investment Fund - and do not fit the description of government agencies. The study recommended that the Saudi regulator quickly issue the draft Commercial Transactions Law, which included an explicit provision to grant state-owned companies, including companies owned by the Public Investment Fund, the status of traders.